PENGARUH ORANG, BUKTI FISIK DAN PROSES TERHADAP KEPUASAN WISATAWAN PADA DESTINASI WISATA PANTAI BULBUL - Silaban, Pantas H. (Jurnal Manajemen dan Bisnis, 2018)
The tourism sector is a strategic sector that can contribute to both regional and national economic growth. This sector can create jobs to increase people's incomes as a consequence of the development of tourism industri and investment. This study investigated the influence of three variables of tourism service marketing mix consisting of people, processes and physical evidence on tourism satisfaction. A total of 53 respondents selected purposively from tourists who have visited at least twice to tourist destinations Bulbul Beach. Using the help of SPSS 18 data software was processed and analyzed and found that people has positively insignificant influence to the satisfaction of tourists, the process has negatively insignificant effect to the satisfaction of tourists, and physical evidence has positively significant effect to the satisfaction of the tourists, with R2 of 0.783. For subsequent research, the studied variables can be expanded into all of the marketing mix variables and more respondents with more tourist visit experience